2016
DOI: 10.1093/hmg/ddw225
|View full text |Cite
|
Sign up to set email alerts
|

Muscle dysfunction caused by loss ofMagel2in a mouse model of Prader-Willi and Schaaf-Yang syndromes

Abstract: Prader-Willi syndrome is characterized by severe hypotonia in infancy, with decreased lean mass and increased fat mass in childhood followed by severe hyperphagia and consequent obesity. Scoliosis and other orthopaedic manifestations of hypotonia are common in children with Prader-Willi syndrome and cause significant morbidity. The relationships among hypotonia, reduced muscle mass and scoliosis have been difficult to establish. Inactivating mutations in one Prader-Willi syndrome candidate gene, MAGEL2, cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 82 publications
1
46
0
Order By: Relevance
“…Scoliosis data for individuals with PWS are wide-ranging, showing a prevalence of 40%–80%, and varying in age of onset and severity 5 38. It has been hypothesised through the use of Magel2 KO mice that MAGEL2 could be the scoliosis-determining gene in PWS 39. In our study, 33% of patients with SYS showed significant scoliosis of >10°, with curvatures of 16°, 52° and 65°.…”
Section: Discussionsupporting
confidence: 46%
“…Scoliosis data for individuals with PWS are wide-ranging, showing a prevalence of 40%–80%, and varying in age of onset and severity 5 38. It has been hypothesised through the use of Magel2 KO mice that MAGEL2 could be the scoliosis-determining gene in PWS 39. In our study, 33% of patients with SYS showed significant scoliosis of >10°, with curvatures of 16°, 52° and 65°.…”
Section: Discussionsupporting
confidence: 46%
“…The reduction in these ambulatory movements may suggest a reduction in anxiety, hypoactivity or a lack of interest toward the novel environment over time. Most recently, this Magel2 knockout mouse was shown to have poor muscle tone due aberrancies in muscle autophagy (Kamaludin et al 2016). This finding may account for some of the observed hypoactivity.…”
Section: Discussionmentioning
confidence: 91%
“…However, despite compromised hypothalamic circuits, mice do not develop hyperphagia or severe obesity, but they do display changes in body composition, such as decreased lean mass and increased adiposity distribution of muscle fiber types and bone mineral content (114, 122-125). This suggests that MAGEL2-dependent pathways may contribute to hypotonia, altered body composition and a high incidence of musculoskeletal abnormalities in PWS and SHFYNG (97, 126-129).…”
Section: Magel2 Mutant Mouse Models Reveal Insights Into Its Physiolomentioning
confidence: 99%